Curate Infirmos: The Medieval Waldensian Practice of Medicine - Biller, Peter (Studies in church history, 1982)
The question posed in this paper is the extent and nature of the medical practice of the medieval waldensian brothers. What lies behind this is in part a historiographical development which gained impetus in the 1960s, principally in the works of Mollat. In these the the period of the late twelfth and early thirteenth centuries has been identified as crucial in several areas: a prise de conscience by many of the problems of material need, whether poverty or physical sickness or other disabilities, and the development of new ideas in some of these areas; a peaking of foundations of institutions of assistance, in particular hospitals for the sick, the outlines of which have become clear in Belgian and French work; the embodiment of the spiritual ideal of poverty in the apostolic religious movements which grew at this time. Mollat has juxtaposed these phenomena in order to suggest that one should look for interconnections between them, and it is in the spirit of his enquiry that the present question is raised. If we look at one of the two major evangelical heresies nurtured in the late twelfth cenury matrix described by Mollat, namely the movement of the waldensian brothers, shall we find an element which should be related to the wider interests and developments in assistance and, in particular, medical care which were displayed elsewhere at this time?